A Strategy to Characterize the LISA-Pathfinder Cold Gas Thruster System. (June 2015) - Armano, M; Audley, H; Auger, G; Baird, J; Binetruy, P; Born, M; Bortoluzzi, D; Brandt, N; Bursi, A; Caleno, M; Cavalleri, A; Cesarini, A; et al.
Abstract: The cold gas micro-propulsion system that will be used during the LISA-Pathfinder mission will be one of the most important component used to ensure the "free-fall" of the enclosed test masses. In this paper we present a possible strategy to characterize the effective direction and amplitude gain of each of the 6 thrusters of this system. A post-publication change was made to this article on 26 Jun 2020 to add an author.